Continuing the Journey Toward Health Equity: Becoming Antiracist in Health Promotion Research and Practice. - Breny, Jean (Health Education and Behavior, 2020)
Health education and promotion researchers and practitioners are committed to eliminating health disparities, and the Society for Public Health Education (SOPHE) has continuously supported this effort through its journals, professional development, annual conferences, and advocacy. The COVID-19 pandemic elucidated inequities directly caused by racism and other social determinants of health. In order to achieve health equity, we need to become antiracist in our research, practice, and advocacy work by standing united against racist policies and practices. I invite us all to heed the call to action on these five points: place racism on the agenda, practice cultural humility, claim your privilege and eliminate microaggressions, utilize strategies that promote inclusion and equity, and embrace your inner leader and activist. Just as SOPHE as an organization pivoted its annual conference from on ground to virtual in March 2020, so can we be innovative and brave as professionals to face the hard work and dedication needed to become antiracist., (C)2020Sage Publications
Keywords: Betacoronavirus; Coronavirus Infections; Coronavirus infection; Health Equity; Health Promotion; Humans; Pandemics; Pneumonia, Viral; Racism; Social Determinants of Health; antiracism; article; dept.pch; ethnology; health education; health equity; health promotion; human; human experiment; leadership; organization and management; pandemic; peer-reviewed; public health; racism; social determinants of health; virus pneumonia